A strategic analysis of Namibia's fiscal policy instruments and measures impact on unemployment and poverty reduction - Kizabi, Christian Kibingwa (2017)
Unemployment and poverty alleviation have been two of the most challenging issues faced by Namibia over the last three decades, and particularly since its independence in 1990. To rectify these two dilemmas the Namibian government introduced many new legislations, innovative fiscal policies as well as structural adjustment initiatives. These were supported by the implementation of three 5-year National Development Plans, with the core aim of propelling rapid employment growth and alleviation of poverty. Despite these efforts, unemployment and poverty remained steadfast, and in many areas increased. This study empirically examined the impact of currently prevailing fiscal policies on the three most important factors of economic development: unemployment, poverty and economic growth. The methodology was based on analysing the Namibian macroeconomic data from the period between 1980 and 2010, employing the tools of cointegration analysis, analysis of Granger causality and the utilization of Vector Error Correction modelling. A number of findings were extracted from the estimation outputs, one of them being the fact that unproductive spending in Namibia has a negative impact on unemployment and economic growth, and at the same time does not help in reducing poverty. It was also found that increasing consumption and social spending discourage positive developments in unemployment dynamics and that advancements in tertiary education are associated with positive shifts in the direction of poverty reduction. Basing on these and other findings, suggested policy improvements are subsequently outlined, one of them being the study recommended the Namibian government to expand the levels of productive spending on education aiming in the first place for the quality of the effect of educational spending, in addition to the quantity.